Improving the Efficiency of Medical Processes Using Process Mining Techniques: An Applied Study on a Healthcare Appointment Scheduling System - مازن محمد إبراهيم السيد; د. الطيب السماني عبد الجبار (White Nile Journal for Studies and Research, 2026)
This applied paper operationalizes the theoretical framework of process mining in healthcare by embedding it into a real appointment-scheduling system. A production-oriented prototype was built using Laravel Framework and MySQL with an Arabic-first UI to capture every relevant event in the appointment journey (create, check-in, start service, end service, cancel, reschedule). The logs were transformed into XES and analyzed using discovery, conformance, and performance perspectives. The application focused on key operational indicators: waiting time, service time, idle time, no-show rate, and doctor utilization. A before/after evaluation showed a reduction in average waiting time, improved resource utilization, and a lower no-show rate after activating dashboards and deviation alerts. These findings are consistent with the healthcare process-mining literature (van der Aalst, 2016) (Muñoz-Gama et al., 2022) (Rojas et al., 2016).